The Influence of Employee Discipline and Competence on Improving Performance at The West Sulawesi Regional Police - Rachmat Pamudji; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the effect of work discipline and employee competence on improving personnel performance at the West Sulawesi Regional Police. The research was motivated by indications of declining performance reflected in fluctuations in internal performance evaluation scores, as well as disciplinary issues such as tardiness, early departure, and unauthorized absences. This study employed a quantitative approach using a survey method involving 92 respondents who were police personnel within the organization, selected through purposive sampling. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results indicate that work discipline has a positive and significant effect on performance, employee competence also has a positive and significant effect on performance, and simultaneously both variables significantly influence personnel performance improvement. These findings suggest that higher levels of discipline and competence contribute to better organizational performance. The study highlights the importance of strengthening disciplinary enforcement and continuous competency development through education and training to enhance performance within the police organization.